Somatic Embryogenesis Formation from Immature Male Flower of Banana cv. Nangka - Puspita Deswina Deswina (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2005)
The plantain banana (cultivar nangka) is among the most valued crop plants in the tropical world. However, the commercially attainable yields are very low compared to other food crops. Somatic embryogenesis has the great potential for rapid and efficient regeneration of plantlets and offers opportunities for large-scale production of plant material. Genetic modification on embryogenic structure offers the opportunity to add desirable gene characteristic. The objective of this study was to evaluate the different medium combination for the induction and optimization of embryogenic formation from immature male flowers. The explants of inflorescence was sampled one month after bunch emergence and approximately 15-20 cm below the last female flower hand. Response of explants and percentage of inflorescence clusters forming nodular callus were recorded and noted. Result of the experiment showed that embryogenic callus could be induced from immature male flowers. The initiation of callus indicated of flower cluster responded to form globular embryogenic callus (49.7% ± 5.2), whereas the percentage of flower cluster responding to form nodular callus was 39.2 % ± 5.3. The highest response of explants forming nodular callus was from flower of rows 12 and 13  (60%).